Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2631-8695/ab899c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, electrical and microstructural studies on nano-TiO2 admixtured cement mortar cured with industrial wastewater

Abstract: Nanotechnology has attracted the attention of building materials over the last decade. Nano-size particles-cement mortar-can positively alter their early and hardened properties. The objective of this study is the inclusion of TiO 2 nanoparticles (NT) as an admixture (2 to 10% by weight of the cement) on the mechanical, electrical, and microstructure properties of cement mortar composites and cured with industrial wastewater. Nowadays, the analysis of TiO 2 nanoparticles in concrete has been recognized increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…This was attributed to the high specific surface area of nanoparticles that adsorbs part of the water and superplasticizer. Gopalakrishnan et al [52] reported a reverse relationship between the content of NT and flow of mortars. Joshaghani et al [35] tested the effect of 3.0 and 5.0 wt% (by weight of the binder) nano-TiO2 on the fresh properties of self-compacting concrete using slump flow, L-box, V-funnel and column segregation tests.…”
Section: Effect On Fresh Propertiesmentioning
confidence: 97%
See 3 more Smart Citations
“…This was attributed to the high specific surface area of nanoparticles that adsorbs part of the water and superplasticizer. Gopalakrishnan et al [52] reported a reverse relationship between the content of NT and flow of mortars. Joshaghani et al [35] tested the effect of 3.0 and 5.0 wt% (by weight of the binder) nano-TiO2 on the fresh properties of self-compacting concrete using slump flow, L-box, V-funnel and column segregation tests.…”
Section: Effect On Fresh Propertiesmentioning
confidence: 97%
“…Titania nanoparticles has been also found to behave as an activator to accelerate pozzolanic reaction, to increase the rate of cement hydration, to increase the intensity of the heat peak, and to reduce the initial and final setting time [14,24,28,37,44,45,52,58,60,61]. The reduction in the setting time was found to be proportional to the content of the added nano-TiO2 [20,40,52,58]. Reduction in setting time could lead to reduction in total time of construction which is economically beneficial [45].…”
Section: Influence Of Incorporation Of Nano-titania Into Cementitious Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the addition of nanomaterials accelerates the hydration process and enhances the formation of C–S–H gel (as marked by yellow hexagons), which makes the microstructure denser, thereby increasing the strength and durability of the treated sample. However, non-uniform dispersion or excessive addition of nanomaterials (beyond an optimum dosage) leads to agglomeration and formation of weak bonds in the mortar sample [ 77 , 148 , 149 , 150 ]. Ling et al [ 13 ] observed that the inclusion of nano-silica in the mortar reduces the pores, concentrates the matrix, and enhances the strength of cementitious composites by improving the adhesion of the hydration products with the PVA fibers.…”
Section: Properties and Methodsmentioning
confidence: 99%